1954
DOI: 10.1128/jb.68.3.338-345.1954
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbohydrates, Proteins, and Bacterial Cells in the Heating Media on the Heat Resistance of Clostridium Sporogenes

Abstract: It is well known that the heat resistance of bacterial spores is influenced markedly by the nature of the medium in which the spores are heated. This fact is an important problem relating to the practical sterilization in bacteriology and in the food industry. Hence voluminous data on the heat resistance of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1955
1955
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…For spores of B. stearothermophilus, a decrease in resistance with increasing concentrations of NaCl up to 8% (w/v) is well established (Cook and Gilbert, 1969;Briggs and Yazdany, 1970) but no report on an increase in resistance with a further increase in NaCl concentrations is known. The very small change in resistance with increasing glucose concentration from 26.5 to 64.3% seems to agree with observations made by Amaha and Sakaguchi (1954) with clostridial spores but is contrary to the relatively large increase reported by Anderson et al (1949) for spores of B. thermoaciduruns.…”
Section: Nonlinearsupporting
confidence: 85%
“…For spores of B. stearothermophilus, a decrease in resistance with increasing concentrations of NaCl up to 8% (w/v) is well established (Cook and Gilbert, 1969;Briggs and Yazdany, 1970) but no report on an increase in resistance with a further increase in NaCl concentrations is known. The very small change in resistance with increasing glucose concentration from 26.5 to 64.3% seems to agree with observations made by Amaha and Sakaguchi (1954) with clostridial spores but is contrary to the relatively large increase reported by Anderson et al (1949) for spores of B. thermoaciduruns.…”
Section: Nonlinearsupporting
confidence: 85%
“…Accordingly the decrease in heat resistance after the long-time storage in sucrose may indicate a slow penetration of the substance into the spores. Serum albumin was in the present study shown to have a protective influence on the dry-heat inactivation of spores, which is in accordance with results found for the moist heat resistance of spores (Amaha & Sakaguchi 1954).…”
Section: Discussionsupporting
confidence: 92%
“…The addition of starch or charcoal increased significantly the recovery of severely heated spores (Table 4, Figs 1,2, 3 and 4). The same effect was observed by Cook & Gilbert (1968), Amaha & Sakaguchi (1954) and Labbe (1970). Adams (1979) classified starch and charcoal as additives which bind inhibitors of germination and outgrowth of heat-injured spores.…”
Section: T H E Effect O F S T a R C H A N D C H A R C O A Lmentioning
confidence: 99%
“…Curran & Evans (1937) and then Olsen & Scott (1946) observed that the character of the survivor curve was significantly affected by the nature of the recovery media. Amaha & Sakaguchi (1954 reported that adding yeast and liver extracts, glucose, fructose, mannose, galactose, sucrose, maltose, soluble starch or pyruvate to the recovery medium increased the apparent heat resistance of Bacillus subtilis spores. Roberts (1970), in a well documented review of the recovery of spores damaged by heat, ionizing radiation or ethylene oxide, outlined the importance of the composition of recovery medium, particularly with respect to starch and calcium dipicolinate content, and the effects of medium pH and the temperature of incubation.…”
mentioning
confidence: 99%